2021
DOI: 10.1039/d1ra03548g
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of poly-dimethyl siloxane formulations with tunable viscoelastic properties

Abstract: We have generated novel formulations of polydimethyl siloxane with varying viscoelastic properties that can be used to study cellular response. We present equations that can be used to predict the storage and loss moduli of these polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…At low strains, Sylgard 527 has previously been shown to be linear elastic 55 . Additionally, the rheological testing (1 rad/s = 0.1592 Hz) and the spontaneously beating μHM (≤1 Hz) both occurred at low frequencies, over which there is little frequency dependence in the shear modulus of Sylgard 527 56 . As such, the dynamic and static modulus should be similar.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At low strains, Sylgard 527 has previously been shown to be linear elastic 55 . Additionally, the rheological testing (1 rad/s = 0.1592 Hz) and the spontaneously beating μHM (≤1 Hz) both occurred at low frequencies, over which there is little frequency dependence in the shear modulus of Sylgard 527 56 . As such, the dynamic and static modulus should be similar.…”
Section: Discussionmentioning
confidence: 94%
“…55 Additionally, the rheological testing (1 rad/ s = 0.1592 Hz) and the spontaneously beating μHM (≤1 Hz) both occurred at low frequencies, over which there is little frequency dependence in the shear modulus of Sylgard 527. 56 As such, the dynamic and static modulus should be similar. This expectation is consistent with our results, which suggested no significant difference between the shear modulus measured using this platform and shear storage modulus measured using the rheometer.…”
Section: Reversibility Of Changes In μHm Physiology Induced By Acute ...mentioning
confidence: 99%
“…Although mechanobiology research has focused on the elastic component of soft tissue mechanical properties, soft tissues in the human body have viscoelastic behaviour. 61 Viscoelasticity is the property of materials that exhibit both viscous and elastic behaviour. 62 The elastic or storage modulus is related to the specimen's stiffness, and the viscous or loss modulus correlates with the specimen's ability to dissipate mechanical energy.…”
Section: Resultsmentioning
confidence: 99%
“…Fromell et al found that more flexible polymer chains seemed to increase protein packing and encourage adsorption of proteins in their native conformation, while stiffer chains encouraged a change in conformation. 51 Here, we have mixed Sylgard 527 which is composed of chains with more repeat units than Sylgard 184, 52 explaining the decrease in elastic modulus seen with increasing amounts of Sylgard 527. It is important to consider when analyzing these results that this method of detection using the EIA determines the exposure of proteins for antibody binding, and functional sites could be hidden on certain substrates due to polymer chain directed changes in conformation when performing adsorption in a competitive plasma protein environment, more representative of what would be experienced physiologically.…”
Section: Fetuin-a Adsorption From Competitive Protein Environment (Pl...mentioning
confidence: 88%